Developing research networks in schools: the role of network intentionality and research engagement - Cornelissen, Frank; McLellan, Ros; Daly, Alan (Frontiers in Education, 2024)
The Anglo-Saxon world has a long history of promoting research engagement with teachers and schools. However, over the years it became evident that building such research engagement in schools is challenging. This study examined factors that may influence the development of research-engaged relationships among colleagues. A survey study, including a social network analysis, was conducted. The findings indicate that both individual educators’ intentional network behavior and their perception of research engagement among school colleagues play a role in educators’ tendency to seek out school colleagues to engage in and with research. More specifically, analyses revealed that educators’ perceived research engagement in school is not mediating the relationship between their intentional network behavior and the size of their research network. This finding could imply that strengthening educators’ intentional network behavior may provide a crucial strategy for boosting the collegial interaction around research in schools.